KOLABORASI GOVERNANCE DALAM PELAKSANAAN TUGAS PEMBANTUAN STUDI PENYALURAN VAKSINASI COVID-19 DI KOTA PEKANBARU TAHUN 2021- 2023 - Efendi, Diminggus; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The Pekanbaru City Health Service Institution is carrying out Collaborative Governance in the distribution of Covid-19 vaccinations with the aim of ensuring that the process of distributing Covid-19 vaccinations in Pekanbaru City runs efficiently and effectively. This research aims to determine the form of Governance Collaboration between Pekanbaru City Health Service Institutions in the distribution of Covid-19 Vaccination, apart from that, it is also to find out solutions so that Governance Collaboration between Pekanbaru City Health Service Institutions can be implemented well in the distribution of Covid-19 Vaccination. Collaboration theory is a general term that is often used to describe a pattern of collaborative relationships carried out by more than one party, apart from that collaboration is not limited by a certain time or period, as long as there are matters that have allusions or intersections with other parties then collaboration remains required. Governance is defined as mechanisms, practices and procedures for government and citizens to manage resources and solve public problems. The research method used is a qualitative method by explaining the data descriptively. The type of research data used is primary in the form of data obtained from research informants and secondary in the form of data obtained from related documents. The informant in this research was Mrs. Selvia Elsih Maser, SKM as Sub Coordinator of Surveillance for Disease Prevention and Control, Pekanbaru City Health Service, Pekanbaru City Community. The results of this research state that the form of Governance Collaboration carried out between Pekanbaru City Health Service Institutions in the Distribution of Covid-19 Vaccination in Pekanbaru City is in the form of Community Health Centers located in each region, where these institutions carry out the function of distributing Covid-19 Vaccination based on regulations. which exists. Even though the realization of the Covid-19 Vaccination process in Pekanbaru City has gone smoothly, in reality the realization of the Covid-19 Vaccination distribution process in Pekanbaru City still has several obstacles. Keywords : Governance Collaboration, Distribution of Covid-19 Vaccination